Ulul Albab’s Paradigm Approach to Post-Conventional Legal Culture of Consumers in Indonesia - Al Munawar, Faishal Agil; Firdaus, Dwi Hidayatul; Musataklima, Musataklima (Fiat Justisia: Jurnal Ilmu Hukum, 2024)
Consumer empowerment in Indonesia, continues to require improvement despite the enactment of Consumer Protection Law Number 8 of 1999, twenty-three years ago. This situation raises questions about why consumer empowerment remains low, its implications for consumer protection, and strategies for reconstruction based on the principles of Ulul Albab. The ulul albab approach to understanding consumer culture and consumer protection in Indonesia emphasizes the importance of integrating knowledge, ethics, and spiritual values. Ulul albab is an Islamic concept referring to individuals who possess deep understanding, wisdom, and critical thinking abilities and who connect rational thought with spiritual awareness. From the ulul albab perspective, consumer culture is viewed not only from a materialistic standpoint or the fulfillment of worldly needs but also from moral and spiritual dimensions. To explore these inquiries, a socio-legal research methodology that integrates sociological, statutory, and conceptual approaches is utilized. Legal materials, including primary, secondary, and tertiary references, contribute to both primary and secondary data. The research findings highlight several critical points. Firstly, the limited empowerment in Indonesia's consumer legal culture is the government's temporary emphasis on consumer education, primarily through socialization. Furthermore, there is a disparity between consumer protection institutions and public, exacerbated by the concentration of LPKSM in urban areas where advocacy often supersedes efforts aimed at empowerment. Secondly, the impact of a weak consumer legal culture on consumer protection is evident in insufficient measures for consumers to safeguard themselves, both preventatively and correctively. Thirdly, the proposed reconstruction of Indonesia's consumer legal culture based on the Ulul Albab paradigm aims to empower consumers through tarbiyah ulul albab, cultivating individuals with comprehensive knowledge, strong moral values, and a robust social conscience.